High‐Performance Hybrid White Organic Light‐Emitting Diodes with Superior Efficiency/Color Rendering Index/Color Stability and Low Efficiency Roll‐Off Based on a Blue Thermally Activated Delayed Fluorescent Emitter. (24th February 2016) - Wu, Zhongbin; Luo, Jiajia; Sun, Ning; Zhu, Liping; Sun, Hengda; Yu, Ling; Yang, Dezhi; Qiao, Xianfeng; Chen, Jiangshan; Yang, Chuluo; Ma, Dongge
Abstract : Thermally activated delayed fluorescence (TADF)‐based white organic light‐emitting diodes (WOLEDs) are highly attractive because the TADF emitters provide a promising alternative route to harvest triplet excitons. One of the major challenges is to achieve superior efficiency/color rendering index/color stability and low efficiency roll‐off simultaneously. In this paper, high‐performance hybrid WOLEDs are demonstrated by employing an efficient blue TADF emitter combined with red and green phosphorescent emitters. The resulting WOLED shows the maximum external quantum efficiency, current efficiency, and power efficiency of 23.0%, 51.0 cd A −1, and 51.7 lm W −1, respectively. Moreover, the device exhibits extremely stable electroluminescence spectra with a high color rendering index of 89 and Commission Internationale de L'Eclairage coordinates of (0.438, 0.438) at the practical brightness of 1000 cd m −2 . The achievement of these excellent performances is systematically investigated by versatile experimental and theoretical evidences, from which it is concluded that the utilization of a blue‐green‐red cascade energy transfer structure and the precise manipulation of charges and excitons are the key points. It can be anticipated that this work might be a starting point for further research towards high‐performance hybrid WOLEDs. Abstract : High‐performance hybrid white organic emitting‐light diodes (WOLEDs) are demonstrated by using an efficient blue thermally activated delayed fluorescent emitter combined with red and green phosphorescent emitters. The resulting WOLEDs show the maximum external quantum efficiency, current efficiency, and power efficiency of 23.0%, 51.0 cd A −1, and 51.7 lm W −1, respectively, with a high color rendering index of 89.